2021
DOI: 10.1039/d1ra01403j
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced phase-alteration in solution processed indium selenide thin films during annealing

Abstract: This article demonstrates the successful synthesis of indium selenide thin films by a spin coating method in air using thiol-amine cosolvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Stresses can induce phase transitions by reducing the transition energy barrier through lattice deformations. , This driving force for phase transition was shown as a positive effect in a nonmetal halide perovskite BaTiO 3 , where a cubic-to-hexagonal phase transition could be forced at relatively lower annealing temperatures with applied tensile stresses . The tensile stress induced a synergistic shear stress above the critical shear stress, inducing lattice slide and a phase transition at a temperature almost 900 °C lower than it would otherwise occur (575 °C vs 1432 °C) .…”
Section: Opportunities For Further Workmentioning
confidence: 99%
“…Stresses can induce phase transitions by reducing the transition energy barrier through lattice deformations. , This driving force for phase transition was shown as a positive effect in a nonmetal halide perovskite BaTiO 3 , where a cubic-to-hexagonal phase transition could be forced at relatively lower annealing temperatures with applied tensile stresses . The tensile stress induced a synergistic shear stress above the critical shear stress, inducing lattice slide and a phase transition at a temperature almost 900 °C lower than it would otherwise occur (575 °C vs 1432 °C) .…”
Section: Opportunities For Further Workmentioning
confidence: 99%
“…MgSe a) CdSe [43][44][45] InSe [ 46,47] GaSe [ 48,49] As grown film structure Cubic Hexagonal Amorphous Amorphous (metal/semiconductor interface) diameter. As the junction diameter is small the electron mobility is considerably higher, resulting in lower series resistance and leading to the highest cutoff frequency.…”
Section: Physical Parametermentioning
confidence: 99%
“…The table also suggests that MgSe has the deepest impurity level and the lowest dielectric constant among other films prepared by the same technique. [42][43][44][45][46][47][48][49]…”
Section: Physical Parametermentioning
confidence: 99%
“…44 Bipanko Kumar Mondal et al achieved a phase change from β-In 3 Se 2 to γ-In 2 Se 3 and also showed an increase in band gap when the annealing temperature was raised to 300 °C along with mechanical stress. 45 Based on the available literature, it is feasible to attain phase change and adjust the band gap of indium selenide at both high and low temperatures. However, there is a lack of research on the use of dynamic pressure to induce phase transformation and tune the band gap in indium selenide.…”
Section: Introductionmentioning
confidence: 99%